EVALUATION OF CHANGE IN NIHSS SCORE FOLLOWING ADMINISTRATION OF INJECTION ALTEPLASE FOR ACUTE CEREBROVASCULAR ISCHEMIA (The Research of Medical Science Review, 2025)
ACI continues to be one of the major precipitating factors for morbidity and mortality all over the world, and there is a call for early and efficient therapeutic management to minimize potential complications. Alteplase (tPA) is the only proven thrombolytic agent used for the treatment of AIS within a limited time frame. The objective of this randomized controlled trial (RCT) study is to assess the effectiveness of alteplase in changing the NIHSS scores in subjects with diagnosed ACI. The sample was collected from Department of Neurology, Sheikh Zayed Hospital, Lahore, Pakistan The patients were selected through a consecutive sampling technique and were randomly divided into treatment and control groups with 43 patients in each group. Eligibility defined the sample as 50-75-year-old patients experiencing their first ACI and NIHSS of between 4 and 15 at admission who received intravenous tPA therapy within 4.5 hours from the onset of symptoms. The mean NIHSS scores at baseline and 24 hours, 7 days, and 90 days after the intervention were the primary end point. Secondary endpoints were the total efficacy rate and the rate of toxic effects at different doses. A predictor analysis showed the NIHSS to be significantly lower in the treatment group compared to the control across all time frames of follow up though the difference was more marked at 24 hours p < 0.001. The total effectiveness rate was significantly superior in the alteplase group, 81.6%, as compared to 61.6% in the control group, p < 0.001. The safety profile of patients in the treatment group was consistent with the reported safety profiles, with a 4% rate of adverse events largely characterized by hemorrhagic transformations. When stratified by subgroups, the analysis showed that patients under 75 years of age, and patients whose baseline NIHSS score was the lowest got more benefits from thrombolytic therapy. This work provides evidence in support of the use of intravenous alteplase to ameliorate the neurological state of ACI patients, which makes it crucial for early administration. The outcomes emphasise the significance of sticking to clinical directions and stress the need for the constant improvement of the approaches related to the strokes as far as their impacts on the patients’ outcomes are concerned.